(untitled) (Damascus University Journal for Sustainable Planning, 2025)
Wastewater treatment technologies have spread that significantly improve environmental performance and helping maintain environmental continuity and sustainability when applied. The most important of these technologies are anaerobic biological treatment and phytoremediation, which is a form of biological treatment. The background of the research emerges by linking two types of treatment technologies (an anaerobic reactor equipped with biological carriers as a primary treatment stage with constructed wetlands as a secondary treatment stage) as a real solution capable of treating raw wastewater at the lowest possible cost. This research aims to evaluate the efficiency of wastewater treatment through these treatment techniques according to local conditions by implementing a pilot treatment plant by relying on reference studies and global experiences that used these techniques as a sustainable option for treatment (from technical and economic aspects). Study the effect of the design parameters for each of the two treatment stages, in the anaerobic reactor (hydraulic residence time, filling ratio of biological carriers, and type of carrier material) and in constructed wetlands (type of flow and type of plant) to reach the best treatment efficiency of this system and the environmental and economic benefits reflected on that. The research will be conducted on the experimental treatment plant at the Faculty of Agriculture at Damascus University as a spatial area for study, and after sampling, the concentrations of pollutants (pH, COD, BOD, TSS) will be experimentally determined. Then analyze the results and link them together in order to prepare a mathematical model linking the organic load and the treatment efficiency of the proposed method, and compare these results with Syrian Standard No. 2752-2008 regarding specifications of treated wastewater for irrigation.